Gallstone Ileus: a Surgical Emergency Presentation - Reinaldo Jiménez Prendes; Rasiel López Echemendia (Medisur)
The case of a 60 years old female patient with a history of gallstones that was admitted as an emergency because of abdominal pain, vomiting and abdominal distension of 2 days is presented. The patient presented also secondary moderate dehydration. In a simple abdominal radiography, radiological signs of intestinal occlusion were found. Electrolyte imbalance was corrected and an exploratory laparotomy was performed. Through this procedure, a large stone was found in the terminal ileum. Enterolithotomy was performed along with enterorraphy, thus solving the occlusion.